What Does Brunei Teach Us About Using Human Development Index Rankings as a Policy Tool? - Bryane Michael (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
The Bruneian Government has set an ambitious target to achieve a top 10 ranking on the UNDP's Human Development Index (HDI) by 2035. To achieve its objective (described in a national strategy document called the Wawasan 2035), Brunei's economy needs to grow by 6%-7%. Is setting an HDI target a good way to govern Brunei's policymaking? Is it a good way to govern any country's policymaking? In this paper, we look at the role HDI-rank targets play on economic and fiscal policy. We show that such a headline target (much like a profit target in a private company setting) automatically sets targets for growth in various economic sectors and fiscal policy targets. As such, HDI-rank targeting may provide a useful mechanism for co-ordinating development policies and for monitoring progress against a wide range development goals using only one number.
Keywords: F63; O11; L74; C61; 330; Human Development; Brunei; Dynamic Optimization; Urban Planning; Development indicator; Brunei